Human GLI3 intragenic conserved non-coding sequences are tissue-specific enhancers. - Amir Ali Abbasi; Zissis Paparidis; Sajid Malik; Debbie K Goode; Heather Callaway; Greg Elgar; Karl-Heinz Grzeschik (PLoS ONE)
The zinc-finger transcription factor GLI3 is a key regulator of development, acting as a primary transducer of Sonic hedgehog (SHH) signaling in a combinatorial context dependent fashion controlling multiple patterning steps in different tissues/organs. A tight temporal and spatial control of gene expression is indispensable, however, cis-acting sequence elements regulating GLI3 expression have not yet been reported. We show that 11 ancient genomic DNA signatures, conserved from the pufferfish Takifugu (Fugu) rubripes to man, are distributed throughout the introns of human GLI3. They map within larger conserved non-coding elements (CNEs) that are found in the tetrapod lineage. Full length CNEs transiently transfected into human cell cultures acted as cell type specific enhancers of gene transcription. The regulatory potential of these elements is conserved and was exploited to direct tissue specific expression of a reporter gene in zebrafish embryos. Assays of deletion constructs revealed that the human-Fugu conserved sequences within the GLI3 intronic CNEs were essential but not sufficient for full-scale transcriptional activation. The enhancer activity of the CNEs is determined by a combinatorial effect of a core sequence conserved between human and teleosts (Fugu) and flanking tetrapod-specific sequences, suggesting that successive clustering of sequences with regulatory potential around an ancient, highly conserved nucleus might be a possible mechanism for the evolution of cis-acting regulatory elements.